The transition from myth to philosophy and the political-formative process of the Greek citizen - Fernandes, Vladimir (Revista Hipótese, 2015)
This article addresses, in general terms, the transition from the mythical thinking to rational philosophical thought and the political-formative process of Greek citizen in the context of the democratic polis. The text is divided in four items, preceded by an introduction. The first exposes some considerations about the characteristics of mythical worldview, that priory the rational logical thought. The second item addresses some factors of social, political and economic sphere, which enable the transition from myth to philosophy, and the emergence of citizenship. The third analyses the consequences, which the new context brings to the new context brings the sphere of education, considering the role played by the sophists, as educators of the polis. The last item considers that the philosophy quickly reveals its political and educational propensity, and therefore the analyzed context can contribute to reflections about philosophical issues of contemporary education.
Keywords: Myth; Philosophy; Citizenship; Education